The Effect of Circuit Training on Dribble Agility in Extracurricular Basketball at SMK Muhammadiyah 1 Pringsewu: Pengaruh Latihan Circuit Training Terhadap Kelincahan Dribble Bola Basket Ekstrakurikuler Smk Muhammadiyah 1 Pringsewu - Ananda, Diva Elviara; Nugroho, Reza Adhi (Universitas Hamzanwadi, 2025)
The purpose of this study was to determine how circuit training affects basketball dribble agility. This study used an experimental design, randomized pretest and posttest group design. The population in this study were all students who were members of the basketball extracurricular at SMK Muhammadiyah 1 Pringsewu, the total population was 40 students and the sample size was 24 students. In this study, descriptive analysis was used to calculate the mean, standard deviation, minimum, and maximum values of student body speed. The results and discussion of the study showed that circuit training was effective in increasing body agility, with an average increase of 4.58 seconds or an increase of 27.19%. The results of data analysis of the treatment group that practiced circuit training experienced a significant decrease in time of 4.60 seconds, while the control group that used the zig-zag run only experienced a decrease in time of 2.86 seconds. This finding answers the problem by showing that circuit training involving a variety of movements and high intensity is more effective in increasing lateral speed, coordination, and muscle strength which are indispensable in dribbling a basketball. The conclusion of this study is that circuit training can significantly improve basketball dribble agility.